View of the Spanish City of Burgos in Civitates Orbis Terrarum and Dissemination of this Image until the 18th Century (Architecture Image Studies, 2025)
The oldest and most famous drawing of the Spanish city of Burgos is the engraving published in the first edition of the city atlas Civitates Orbis Terrarum published in Antwerp in 1572. This view, attributed to the Flemish painter Joris Hoefnagel (1542-1600), lacks the chorographic and architectural precision of the other Spanish views made by this artist during his stay in Spain between 1563 and 1567. This image of Burgos was spread throughout Europe in successive editions of Civitates Orbis Terrarum from 1572 to 1617, and it was a model for later engravings that used this atlas as a reference until the 18th century. A graphic analysis of the drawing, comparing it with the view of the city made by Anton Van der Wyngaerde (1512-1571) in 1565, reveals that Hoefnagel's drawing was a graphical interpretation of the city made afterwards in Antwerp, when preparing all the views for atlas editing, rather than a drawing made from a graphic surveying of the city.